KETEKUNAN NELAYAN DALAM NOVEL KARYA HEMINGWAY THE OLD MAN AND THE SEA (DISKUSI PERBANDINGAN PERSPEKTIF BUDAYA MAKASSAR) - Tahir Tahir; Fathu Rahman; Herawaty Abbas (Musamus Journal of Language and Literature, 2020)
This study aims to (1) find out the persistence concept of fisherman as described in the Old man and the Sea novel viewed from Makassar perspective, (2) find out the concept similarity and different concept between two different cultures. This study used a qualitative method to analyze a text in the novel and viewed it from Makassar perspective by taking a reference book of discussing the Makassar culture and then study from a cultural perspective of Makassar to strengthen this research, the research also interviewed to fisherman as addition data. The finding indicated that there are four concepts on how persistent of a fisherman in catching fish. The four concepts are 1) struggle, 2) sacrifice, 3) personal concern, and 4) religious obedience. There are similarities and difference in these four concepts from two different cultures is struggle and sacrifice.